Upaya Preventif Hipertensi Dan Hiperkolesterolemia Melalui Penyuluhan Gizi-Farmasi Dan Pembuatan Empon-Empon Di Desa Argo Mulyo - Fahrul Rozi; Putri Anggraeni; Laode Rijai; Hifdzur Rashif Rijai; Venna Shintary (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Hypertension and hypercholesterolemia are diseases whose prevalence is still relatively high in Indonesia. One of the provinces with the highest incidence of hypertension and hypercholesterolemia in Indonesia is East Kalimantan. Treatment and prevention of hypertension and hypercholesterolemia can be done modernly or traditionally. However, traditional treatment is considered cheaper and safer to use. One of the traditional efforts to prevent hypertension and hypercholesterolemia can be done by using family medicinal plants (TOGA). In order to be effective and efficient, prevention of hypertension and hypercholesterolemia must be equipped with sufficient knowledge. One source of knowledge is obtained from education about hypertension and hypercholesterolemia. Counseling is one part of community service activities. Therefore, this activity was carried out with the aim of increasing public awareness of hypertension and hypercholesterolemia, so that people can carry out treatment and prevention by utilizing potential plants around the house independently. This activity involved 40 people from Argo Mulyo Village, Sepaku District, North Penajam Paser Regency, East Kalimantan Province. The results of this activity show that the community has increased knowledge related to hypertension and hypercholesterolemia as indicated by higher posttest results compared to the pretest. The community was also very enthusiastic and responded well during the counseling and demonstration on making empon (herbal drink).